Data Journalists Using Facebook - Appelgren Ester (Nordicom Review, 2016)
On Facebook there are interest groups created by journalists, for journalists, that focus on the journalistic profession and work methods. One example is the Swedish group, “Datajournalistik” (in English, “Data Journalism”), which was created in 2012. This article builds on Granovetter’s theory on the strength of weak ties and is focused on the skill development process taking place in the group. A content analysis has been carried out of all posts that received comments in order to explore the social functions of the group. The results indicate both a significant need for knowledge exchange and a need for self-affirmation. At the time of the study, the group was unique in the Nordic countries and as such has played a major role in data journalism’s development process in the Nordic region.